(untitled) (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to determine the effect of using the Wordwall educational game medium on the learning outcomes of fourth-grade students in the Natural and Social Sciences (IPAS) subject at SDN 2 Bandorasawetan. The study employs a quantitative approach using a pre-experimental method and a One-Group Pretest-Posttest design. The study population consisted of 28 fourth-grade students, all of whom were included in the sample using a total sampling technique. Data were collected through observation, interviews, documentation, and written tests (pretest and posttest). Data analysis was conducted using the Paired Samples T-Test and the Normalized Gain (N-Gain) test with the aid of SPSS version 25. The results indicate a significant difference between learning outcomes before and after the use of the Wordwall medium, with a t-value of 17.547 and a significance level of 0.000 (p < 0.05). The N-Gain test results showed an average score of 0.78 (or 77.95%), falling into the "highly effective" category. Thus, the use of the Wordwall educational game medium has a significant and effective impact on improving the learning outcomes of fourth-grade students in the IPAS subject at SDN 2 Bandorasawetan.